Key regulatory genes in sugar beet's defense against curly top virus identified by network analysis and qRT-PCR - Zeinab Porameri; Abozar Ghorbani; Zahra Mirsoleymani; Marzieh Karimi; Mahsa Rostami; Seyed Ali Hemmati (Biochemistry and Biophysics Reports)
Curly top disease, caused by Beet Curly Top Virus (BCTV), is a major threat to sugar beet (Beta vulgaris), resulting in significant yield losses. This study integrates RNA sequencing, gene network analysis, and experimental validation to uncover key regulatory genes involved in plant responses to viral infection. Network analysis identified nine central hub genes associated with fatty acid metabolism, stress adaptation, and transcriptional regulation. Meanwhile, functional enrichment analysis highlighted chloroplast-associated immune signaling, oxidative stress modulation, and secondary metabolite biosynthesis as critical defense mechanisms. Due to the genomic similarities between BCTV and Beet Curly Top Iran Virus (BCTIV), BCTIV was selected to investigate whether conserved molecular responses exist in sugar beet infected by these phylogenetically related viruses. The upregulation of hub genes - Su1 (EMB3147), Su2 (FRS5), and Su3 (LACS9)- under BCTIV infection was found to mirror patterns observed in BCTV-infected plants, suggesting convergent defense mechanisms against both viruses. A strong correlation (R2 = 0.995) between qRT-PCR and RNA-Seq data further confirmed that the close genomic proximity of BCTIV to BCTV results in analogous transcriptional reprogramming in the host, supporting the broader relevance of these findings for curly top disease management.